Transition to adult services. Issue 3 (6th October 2011) - Gleeson, Helena; Turner, Gill
Abstract : The lack of focus on young people as a group with particular healthcare needs in medical training and the health service underpins the difficulty that we have experienced as a profession in improving transition in the UK. This article discusses current progress towards improving training in young people's health in the UK, the evidence base for transitional care in young people with chronic conditions with interventions that focus on staffing, service delivery and young people, a practice based approach for transitional care in young people with learning difficulties and complex needs, the need for monitoring and evaluation of transitional care, and the challenge of funding.